Fabrication of High Efficiency Green InGaN/GaN MicroLEDs by Modulating Potential Barrier Height of the Sidewall MQWs in V-Pits - Hsin-Yu Liu; Donghao Zhang; Zhongying Zhang; Chaohsu Lai; Zongmin Lin; Chia-En Lee; Lijun Bao; Sheng-Po Chang; Shoou-Jinn Chang (IEEE Photonics Journal, 2024)
In this study, Green MicroLEDs with different H2 flow during the barrier growth are investigated. We observe that the Indium composition near V-pits affects potential barrier height of the sidewall multiple quantum wells (MQWs) thus has strong impact on screening effect of V-pits. EQE and relative IQE has a dramatically increase with more hydrogen flow during barrier growth, and thermal endurance and wavelength stability was also improved. The enhancement has been confirmed to come from the reduction of non-radiative recombination centers from small V-pits and higher potential barrier height on sidewall MQWs in V-shaped pits which screen dislocations (TDs). These results demonstrate the advantages of modification H2 flow during barrier growth and also provide a new concept to modulate potential barrier height of the sidewall MQWs for better screening effect for further improvement on MicroLEDs performance.